2017
DOI: 10.1021/acs.jpcb.7b07945
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Differential Interaction of Protic and Aprotic Ionic Liquids inside Molecular Confinement

Abstract: Considering the contemporary interests of water-free reverse micelles (RMs) in the field of organic reaction medium and potential drug delivery carrier, we synthesized two different classes of ionic liquids (ILs), protic N-methyl-2-pyrrolidonium hexanoate, [NMP][Hex], and aprotic choline hexanoate, [Chl][Hex], and subsequently incorporated them in a mixture of polyoxyethylene (20) sorbitan monooleate (Tween-80) and cyclohexane. In order to understand the differential nature of interinterionic interaction of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…From another aspect, according to Bronsted's acid-base theory, PIL are produced from proton transfer from acid to base. [18] Usually, an IL is composed of an organic cation, which may include one or more substituted alkyl chains [R = [CH3(CH2)]nC (nC (carbon number)= 8-20)]; and an organic or inorganic anion. As an illustration, one has alkyl imidazolium [R 1 R 2 mim] + or tetraalkylammonium [NR4] + , associated with tetrafluoroborate (BF4)or chlorine (Cl) -(Fig.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…From another aspect, according to Bronsted's acid-base theory, PIL are produced from proton transfer from acid to base. [18] Usually, an IL is composed of an organic cation, which may include one or more substituted alkyl chains [R = [CH3(CH2)]nC (nC (carbon number)= 8-20)]; and an organic or inorganic anion. As an illustration, one has alkyl imidazolium [R 1 R 2 mim] + or tetraalkylammonium [NR4] + , associated with tetrafluoroborate (BF4)or chlorine (Cl) -(Fig.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…Crosio et al showed that certain bimolecular nucleophilic substitution reactions (S N 2) can be promoted in the confined environment of EAN/benzyl- n -hexadecyl­dimethyl­ammonium chloride/toluene-based RM systems . Although Kusano et al and Panda et al have compared the properties of protic and aprotic IL-based water-in-IL and IL-in-oil microemulsions, respectively, the delicate microenvironment and the role of H-bonding in the observed superiority of the protic IL-based systems were overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…33 Crosio et al showed that certain bimolecular nucleophilic substitution reactions (S N 2) can be promoted in the confined environment of EAN/benzyln-hexadecyldimethylammonium chloride/toluene-based RM systems. 34 Although Kusano et al 35 and Panda et al 36 Synthesis of Ionic Liquids (ILs) and Characterization. We have synthesized protic IL, 1,1,3,3-tetramethylguanidinium salicylate ([TMG][Sal]) and aprotic IL, cholinium salicylate [CHO][Sal] by neutralization of 1,1,3,3-tetramethylguanidine (TMG) and cholinium hydroxide (CHO), respectively, with salicylic acid (Figure S2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…They have the ability to accept and donate a proton and form an extended 3D structure. 73 Phosphonium and pyridinium based ionic liquids are referred as PIL’s. 71 PIL’s have comparatively low cost and are easy to synthesize according to the application.…”
Section: Introductionmentioning
confidence: 99%